PENGEMBANGAN MEDIA PEMBELAJARAN E-KOMIK PADA MATERI GAYA KELAS IV DI SEKOLAH DASAR - Alda Indah Syafitri; Nana Hendracipta; Encep Andriana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop an e-comic learning medium for fourth-grade elementary school students on the topic of style and to determine its feasibility. The background of this research is the low interest of students in learning abstract science and science subjects. Therefore, an engaging and easy-to-understand learning medium is needed. The R&D (Research and Development) method was used in this study, and the procedure applied the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation. The trial subjects were 22 fourth-grade students at SDI Baitul Salam. Data were obtained through a validation questionnaire conducted by material experts and media experts. The media expert validation results obtained a percentage of 80.5%, categorized as